2020
DOI: 10.1556/066.2020.49.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Extraction of Betalain Compounds From Beetroot Peels With Aqueous Ethanol Solvent

Abstract: Consumer concern over artificial food additives has stimulated production of pigments from natural sources. The aim of this study was to examine the effects of process variables on the content of colour compounds (betaxanthin and betacyanin) in beetroot peel juice extracted by conventional method. In this research, the extraction processes were carried out according to the central composite design with different process variables. Quantitative measurements of the basic colour compounds in beetroot extract were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…Li et al [9] determined the betalain content in three amaranth species and in different parts of the plant, obtaining the maximum content of 20.93 mg/100 g d.m in Amaranthus caudatus leaves in an extraction time of 15 h. Das et al [13] reported a maximum content of 159.09 mg/100 g d.m in 60 min from foliage of Amaranthus cruentus . However, Maran et al [14] reported a maximum content of total betalains of 41.54 mg/100 g d.m in an extraction time of 115 min in Opuntia ficus-indica fruit, whereas Zin et al [15] obtained maximum concentrations of betacyanins and betaxanthins in 1 h in beetroot peels. Although these studies have been of great importance regarding the extraction and characterisation of betalains in different sources, it is noteworthy that high pigment concentration is achieved in long extraction times, which leads to higher energy consumption.…”
Section: Introductionmentioning
confidence: 98%
“…Li et al [9] determined the betalain content in three amaranth species and in different parts of the plant, obtaining the maximum content of 20.93 mg/100 g d.m in Amaranthus caudatus leaves in an extraction time of 15 h. Das et al [13] reported a maximum content of 159.09 mg/100 g d.m in 60 min from foliage of Amaranthus cruentus . However, Maran et al [14] reported a maximum content of total betalains of 41.54 mg/100 g d.m in an extraction time of 115 min in Opuntia ficus-indica fruit, whereas Zin et al [15] obtained maximum concentrations of betacyanins and betaxanthins in 1 h in beetroot peels. Although these studies have been of great importance regarding the extraction and characterisation of betalains in different sources, it is noteworthy that high pigment concentration is achieved in long extraction times, which leads to higher energy consumption.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, care should be made for subsequent pigment compartmentalizations. The scavenged amounts of BX are about two or three times lower than BC which might be either due to their natural occurrence portion [30] or the processing conditions that have affected their degradation as well. Hence, the quantity of betaxanthin in the pressed juice and the extract was double as to betacyanin in the study of Slavov and co-workers [31].…”
Section: Discussionmentioning
confidence: 95%
“…In the UV visible region, betaxanthin and betacyanin are detectable at the maximum wavelength absorption of 480 and 540 nm, respectively [27]. Betacyanin is responsible for the red color but also more tolerant to heat and stable to processing conditions than the yellow color giving betaxanthin [3,9,39].…”
Section: Betalainsmentioning
confidence: 99%
“…Heating mode, duty cycle, power or heat energy, and temperature in an advanced microwave set up are basic operational parametric modes in MAE of betalains and phenolic compounds. Response surface methodology (RSM) is a suitable tool to approach the efficiency of MAE through the interaction of process variables despite the fact that the predicted values estimated by the model are only within the experimental limit [9,18,62,63,[67][68][69][70][71][72][73]. Central composite design was mostly chosen for the investigation of each or parallel effects of process variables on the corresponding response.…”
Section: Microwave-assisted Extraction (Mae) Of Betalains and Phenolimentioning
confidence: 99%
See 1 more Smart Citation